Constraints Affecting the Teachers’ Job Satisfaction of Odisha University of Agriculture and Technology, Odisha - Jayasingh, Debi Kalyan; Gowda, N. S. Shivalinge; Tripathy, Maitreyee; Nandy, Avisweta (Indian Journal of Extension Education, 2022)
The study was conducted in three campuses of Orissa University of Agriculture and Technology, Bhubaneswar viz. Bhubaneswar, Chiplima and Bhawanipatna in 2019 to find out constraints affecting the job satisfaction along with the suggestions for improving the job satisfaction of teachers working in the University. Ninety respondents from these three campuses were selected for the study using a random sampling procedure. Data was collected from the respondents by implementing personal interview method. Majority of the respondents state that the constraints like lack of enough teaching staff, duty related workload, insufficient staff quarters and shortage of lands for research and practical classes were prominent in hampering their job satisfaction. The suggestions for solving the constraints predominantly suggested were teachers’ recruitment for workload optimization, adequate staff quarters, sanctioning adequate funding along with lands for research.
Keywords: Teachers; Job satisfaction; Agricultural university; Constraints; Problems; Organization